APPLICATION OF GIS TECHNOLOGY FOR FISHING GROUND FORECASTING OF TUNA FISH IN VIETNAM SEA WATERS - Thuoc, Pham; Thanh, Nguyen Duy (Vietnam Journal of Marine Science and Technology, 2012)
In recent years, the map for forecasting of tuna (big eyes tuna and yellow fins tuna) fishing grounds has based upon fisheries data of longline gear which were collected through different projects from the period of 1996 to 2010. These data resources have been restoring at the Research Institute for Marine Fisheries (RIMF). Both univariate time series models and overlapping organized maps method were used in order to identify tuna fishing grounds by using geographical information system (GIS) tecnology based upon fisheries data of the catch per unit of effort (CPUE). The CPUE was seemed to be main index for pointing out the potential areas for high concentration of tuna and evaluating the spatial distribution patterns of this species by season and time series. The spatial distribution patterns were equally limitted by the distance between  longitute and latitute (30 by 30 nautical mile). The results of the fishing ground forecasting of tuna species in recent years reproduced main fishing grounds of this species. In addition, these results are comprehensively evaluated about changing trend of both spatial distribution and time series simultaneously. Furthermore, review of the results of this work in the period from 2000 to 2010 will be not only bring catching efficiency at that time but also significantly providing scientific information bases for fishing guidance and forecasting further.